Wild planet 1,001 extraordinary events for the inspired traveler - Clynes, Tom (New York Gale Research, 1995)
"A collection of the earth's amazing moments: festivals,celebrations, ceremonies, and other gatherings that capture locales when they're at their most brilliant, open,artistic, musical"--P. xiii.
Includes index.
Keywords: Festivals -- Directories; Holidays -- Directories; Special days -- Directories